2009
DOI: 10.1097/wnp.0b013e3181c2bcc8
|View full text |Cite
|
Sign up to set email alerts
|

The Auditory System Involvement in Parkinson Disease: Electrophysiological and Neuropsychological Correlations

Abstract: In the course of Parkinson disease (PD), apart from motor symptoms, presence of mental disturbances such as dementia and depression is common. The aims of this study were to assess the auditory system involvement in patients with PD using electrophysiological and neuropsychological tests and to correlate the cognitive impairment and the auditory evoked potentials tests results. The auditory and cognitive functions were studied in 53 patients with idiopathic PD, mean age 65.8 +/- 9.1 years; mean disease duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The high-frequency hearing impairment associated with PD was detected in the current work similar to prior studies ( 26 28 ). Impaired hearing in PD was attributed to peripheral auditory dysfunction ( 27 , 28 ) and abnormal central auditory processing ( 29 , 30 ). Likewise, abnormal BAEPs among PD patients were demonstrated inconsistent to previous studies, denoting brainstem auditory conduction delay ( 26 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-frequency hearing impairment associated with PD was detected in the current work similar to prior studies ( 26 28 ). Impaired hearing in PD was attributed to peripheral auditory dysfunction ( 27 , 28 ) and abnormal central auditory processing ( 29 , 30 ). Likewise, abnormal BAEPs among PD patients were demonstrated inconsistent to previous studies, denoting brainstem auditory conduction delay ( 26 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, correlation of other non-motor features poorly linked to brainstem dysfunction such as cardiovascular symptoms, attention/memory, and perception/hallucination could be explained by associated disease severity ( 42 ). Cognitive deficits of PD are correlated to higher order auditory processing in subcortical–cortical pathways evaluated by event-related potentials (P300) ( 29 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Middle latency auditory evoked potentials are abnormal in most PD patient. P300 is absent significantly more often in PD patients with cognitive impairment [64].…”
Section: Parkinson Diagnosismentioning
confidence: 91%
“…UPDRS I scores evaluates losses in mental functions (mentation, behavior and mood) that influence the generation of P300 10,24 . Previous studies have shown a positive correlation between the prolongation of P300 latencies in PD and deficits in memory, attention, executive functions, and depression 6,7,25,26 . The authors suggest that prolonged P300 latencies are correlated to cognitive impairment 7 and behavioral problems 27 in PD patients.…”
Section: Discussionmentioning
confidence: 99%